2016
DOI: 10.1080/07359683.2016.1199206
|View full text |Cite
|
Sign up to set email alerts
|

The preventative power of “pink”: Delineating the effects of social identification and protection motivation theory in breast cancer-related advertisements

Abstract: An online experiment was conducted to assess the extent gender-salient breast cancer awareness advertisements had on influencing risk perception, encouraging preventative behaviors, and gathering health information. Social identification theory and protection motivation theory postulate gender-salient pink-branded advertisements trigger defense mechanisms, countering desired outcomes. This study concludes gender-salient ads focusing on women, and displaying the Susan G. Komen logo caused aversive behaviors, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…For men to engage with cancer prevention information, they must perceive it as relevant to them; thus, the content and information transmission processes need to be nuanced to reflect gender, generational, and ethnic differences. Moreover, information needs to be developed in both gender‐specific and gender neutral formats where appropriate, as it has been shown that gender‐specific information can have adverse effects on a number behaviors related to cancer prevention and information‐gathering among women . It is also essential that the target audience, preferred learning strategies, social networks, and daily sphere of information are considered when designing health promoting interventions …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For men to engage with cancer prevention information, they must perceive it as relevant to them; thus, the content and information transmission processes need to be nuanced to reflect gender, generational, and ethnic differences. Moreover, information needs to be developed in both gender‐specific and gender neutral formats where appropriate, as it has been shown that gender‐specific information can have adverse effects on a number behaviors related to cancer prevention and information‐gathering among women . It is also essential that the target audience, preferred learning strategies, social networks, and daily sphere of information are considered when designing health promoting interventions …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, information needs to be developed in both gender-specific and gender neutral formats where appropriate, as it has been shown that gender-specific information can have adverse effects on a number behaviors related to cancer prevention and information-gathering among women. 76 It is also essential that the target audience, preferred learning strategies, social networks, and daily sphere of information are considered when designing health promoting interventions. 40,68,70 While older men might benefit from simple interventions that do not involve complex technologies, 75 interactive and visually appealing interventions can be used successfully to target younger men.…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…The importance of this study is underscored by evidence suggesting the overuse and overcommercialization of “Pink” campaigns have generated negative feelings toward BCAM (Elliott, 2007), resulting in a decrease in preventive behaviors (Puntoni, Sweldens, & Tavassoli, 2011) and risk perception among at-risk women (Devlin & Dillard, 2016). Despite the seemingly good intentions and the amount of donations received, the NFL has been accused for “pinkwashing,” (Sinha, 2014) a term used to refer to a company’s implicit or explicit use of “pink” to sell merchandise benefiting the company rather than the cause (Sulik, 2010).…”
mentioning
confidence: 99%